1993
DOI: 10.1042/bj2910793
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diosgenin on biliary cholesterol transport in the rat

Abstract: Biliary cholesterol output in rats was stimulated over 3-fold by feeding diosgenin for 5 days, whereas biliary outputs of phospholipid and bile salts were not changed by diosgenin feeding. Isolating and perfusing the liver without bile salts resulted in a rapid and substantial decrease in biliary bile salt output; bile salt depletion abolished the diosgenin-induced increment in biliary cholesterol output, showing that the diosgenin-elevated biliary cholesterol output was bile-salt-dependent. Diosgenin treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 31 publications
4
9
0
Order By: Relevance
“…The inhibition effect on PDE is unlikely due to diosgenin and this may suggest a cholesterolrelated change in the normal distribution or function of some membrane constituents destined for biliary excretion. The decrease in this enzyme activity may also be involved in the formation or exocytosis of phospholipid/ cholesterol vesicles from the canalicular membrane to bile; this is in agreement with the observations of Thewles et al [19]. The microsomal fraction which was expected to contain putative biliary type vesicles was subselected for density gradient centrifugation.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The inhibition effect on PDE is unlikely due to diosgenin and this may suggest a cholesterolrelated change in the normal distribution or function of some membrane constituents destined for biliary excretion. The decrease in this enzyme activity may also be involved in the formation or exocytosis of phospholipid/ cholesterol vesicles from the canalicular membrane to bile; this is in agreement with the observations of Thewles et al [19]. The microsomal fraction which was expected to contain putative biliary type vesicles was subselected for density gradient centrifugation.…”
Section: Discussionsupporting
confidence: 80%
“…Previous publications have shown that feeding with diosgenin for 7 days leads to cholesterol saturation in bile [12,19,40]. In our study, diosgenin increased biliary cholesterol over 3 fold (Tab.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Isolating and perfusing the liver without bile salts resulted in a rapid and substantial decrease in biliary bile salt output; bile salt depletion abolished the diosgenin-induced increment in biliary cholesterol output, showing that the diosgenin-elevated biliary cholesterol output was bile-saltdependent. 66 Diosgenin and beta-sitosterol were administered to CRJ/CD male mice for 15 days, the changes in bile acid metabolism was examined. This resulted with some differences between diosgenin and beta-sitosterol in their effects on diet intake, liver weight, and plasma cholesterol level.…”
Section: Effect Of Diosgenin On Metabolic Processmentioning
confidence: 99%
“…Greater yam tuber contains viscous mucilage which consists of soluble glycoprotein, dietary fiber, and saponin (diosgenin) (Thewles et al, 1993;Jenkins et al, 2001). Greater yam tuber has different flesh color including purple, yellow, and white.…”
Section: Introductionmentioning
confidence: 99%